KONSEP KEMAMPUAN ALLAH (QUDRATULLAH) DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Supriyadi, Asep; Suhartini, Andewi; Nurwadjah, Nurwadjah (LPPM STAI Al-Azhary Cianjur, 2022)
This study aims to determine the concept of Allah's Ability (Qudratullah) and its implications for Islamic Education. This study used a qualitative approach with the library research method (library research). This research is focused on the verses of the Qur'an related to the Asmaul Husna Al-Qadir and Al-Muqtadir as part of the conception of Allah's Ability (Qudratullah). There are several implications that can be drawn from the concept of God's Ability (Qudratullah) and in Islamic Education: (1) The teaching (material/content) of Islamic education cannot be separated from the theological basis of monotheism. (2) The development of science in Islamic education can be obtained by using kaun (nature), as well as a vehicle to strengthen faith. (3) Humans are able to plan, predict and God determines. Therefore, humans are led to strengthen efforts and prayers, including in the educational process. (4) Ownership is directly proportional to control. In the context of education, for example, if someone wants to master science, it is necessary to have a way of getting and wasilah that can lead to knowledge. (5) the will requires the ability (mastery) of something. Ability+Will=Result. For a successful educational process, ability and desire are needed.